Outside Options and the Failure of the Coase Conjecture - Board, Simon; Pycia, Marek (American Economic Review, 2014)
A buyer wishes to purchase a good from a seller who chooses a sequence of prices over time. Each period the buyer can also exercise an outside option, abandoning their search or moving on to another seller. We show there is a unique equilibrium in which the seller charges a constant price in every period equal to the monopoly price, contravening the Coase conjecture. We then embed the single-seller model into a search framework and show the result provides a foundation for the usual “no haggling” assumption. (JEL C78, D42, D43, L12, L13)